Development of Podcast-Based Learning Media on the Material of Healthy Associations in Subjects Pjok Class X Sma Negeri 2 Bengkulu Tengah - Susanto, Putra Rengki Hendro (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to produce podcast-based learning media on healthy social intercourse material in class X PJOK subject SMA Negeri 2 Bengkulu Tengah. This research is research and development or development research, with a development model using the ADDIE model. The ADDIE model development steps are as follows (1) Analysis (2) Design (3) Development (4) Implementation (5) Evaluation. The formulation of the problem of this study is how the development of podcast-based learning media on healthy social intercourse material in class X PJOK subjects SMA Negeri 2 Bengkulu Tengah. Data collection is done by means of observation, interviews, documentation and questionnaires. Quantitative data analysis was carried out using a questionnaire assessment score using a five Likert scale. The validity of this learning media was assessed by a team of experts, namely material experts and media experts, as well as student responses. The validity of the media has an average score of 3, 83 with a very valid category, the validity of the material with an average score of 3, 9 with a very valid category, and 4, 21 the average score of student responses.